Real‐time experimental study and numerical simulation of phase change material during the discharge stage: Thermo‐fluidic behavior, solidification morphology, and energy content. Issue 1 (29th April 2019) - Soni, Vikram; Kumar, Alok; Kumar, Arvind; Jain, Vijay Kumar
Abstract: This article experimentally and numerically investigates solidification behavior of a phase change material during the discharge stage. Particle image velocimetry technique is used to measure the real‐time flow field. The visualization and measurement of solidification characteristics (solidifying interface, mushy zone, solidifying morphology—columnar, and equiaxed dendrites, etc.) are carried out using a high‐resolution camera. Transient temperature at strategic locations is measured using instrumented thermocouples. Experimental results observe multiple rotating vortices and thermal plumes due to Rayleigh‐Bénard convection currents. An interesting phenomenon of detachment of dendrite flakes from the developing mushy zone is observed, which provides several nucleation sites for the initiation of the solidification and leads to heat transfer enhancement. Numerical simulations are performed using a one‐domain continuum model. A comprehensive description of the local and the global scale behavior of solidified fraction, thermal field, and flow field is provided, and their role on energy discharge is established. The energy discharge rate from the system is quantitatively computed using thermal performance indicators, such as latent energy, total (sensible + latent) extracted specific energy, and specific power. Abstract : PIV experimental setup, thermo‐fluidic behavior, solidification morphology, and energy content 1. Real‐time flow field, solidification morphology, and transient temperature response during the discharge stage of phase change material are experimentally determined and numerically simulated 2. Detachment of dendrite from the developing mushy zone leading to heat transfer enhancement 3. Solidified fraction, thermal field, and flow at local and global scale are described, and their role on energy discharge is established using thermal performance indicators